ANALISIS MANAJEMEN PERSEDIAAN OBAT DENGAN METODE ABC-VEN DI RUMAH SAKIT YASYFIN DARUSSALAM GONTOR - Wiro Patabi; Zaenal Fanani; Istianatus Sunnah; Arrasyid Indra Muliawan (Universitas Banten Jaya, 2026)
Drug inventory management is an important component in ensuring the quality of health services in hospitals. Inaccuracies in management can lead to stock vacancies or budget waste. The purpose of this study is to analyze the management of drug supplies using the ABC-VEN method at the Pharmaceutical Installation of Yasyfin Darussalam Gontor Hospital. This type of research is descriptive research of data collection carried out retrospectively using quantitative data. The data used is drug use data for the January-December 2025 period which is analyzed using the ABC, VEN, and ABC-VEN matrix combinations. The results showed that the ABC analysis based on the usage value consisted of group A as many as 59 items 8.91% with a total usage of 70.91%, group B of 88 items of 13.29% with a total usage of 20.05%, and group C of 515 items of 77.79% with a total usage of 9.04%. Based on the investment value, category A 98 items 14.80% with an investment value of 70.92%, group B 174 items 26.28% with an investment value of 20.07, group C 390 items 58.91% with an investment value of 9.02%. VEN analysis showed 87 items of 13.14% including vital, 471 items of 71.15% essential, and 104 items of 15.71% nonessential. The results of the analysis based on the combination of ABC and VEN methods showed that in the VA category as many as 25 items the number of items was 3.78%, the VB group was 23 items 3.47%, the BE group was 124 items 18.73%, the VC group was 38 items 5.74%, the group was 65 items were 9.82%, the EB group was 124 items 18.73%, the EC group was 283 items 42.75%, the NA group was 8 items 1.21%, NB group as many as 28 items 4.23%, CN group as many as 68 items 10.27%. Keywords: ABC-VEN Analysis, Drug Supplies, Pharmaceutical Installations, Hospitals